Gate leakage current sensing for in situ temperature monitoring of p-GaN gate HEMTs. (November 2020) - Borghese, A.; Riccio, M.; Longobardi, G.; Maresca, L.; Breglio, G.; Irace, A.
Abstract: In this paper, an effective, yet simple, methodology for the temperature monitoring of voltage-driven p-GaN HEMTs based on gate leakage current sensing is presented. The proposed solution has been verified by SPICE electrothermal simulations and experiments on commercial devices within and out of safe operating area (SOA). Moreover, the monitoring circuit can be effectively adopted for commercially available normally-off p-GaN HEMTs with no need of modifying the recommended gate driver circuit. Highlights: Gate leakage current of normally-off p-GaN HEMT shows a remarkable dependence on the temperature and on the gate bias. Simple gate driver circuit to monitor the HEMT temperature was designed and tested by SPICE electrothermal simulations. The circuit does not bring an additional design burden to the gate driver.